Number Poetry: An Interdisciplinary Proposal / Poesia dos números: uma proposta interdisciplinar - José Erlandson Kaique Lima dos Santos; Gêrlan Cardoso da Silva (Universidade Estadual de Alagoas, 2017)
: Nowadays, mathematics teaching is often transmitted in a disjointed way with the student's reality, making him like discipline A or B. From this view it was observed that an interrelation between the different disciplines is necessary Offered during the school life of the student so that he has a broader experience on the areas of knowledge. The objective of this article was to report the proposal that was offered in a workshop entitled: Poetry of Numbers presented at the 1st Seminar of Letters of PROESP / UNEAL on November 2 of the current year and propose a reflection, suggestion and interdisciplinary evaluation for the integration Between Language and Number. Then it was reported the experience that graduates in Letters of the Special Program for Training of Public Servants of the State University of Alagoas - UNEAL had during their participation in the proposal. It was developed as follows: An initial discussion about what Mathematics and Literature is? Following the presentation of all the theoretical reference on the subject in question, and finally the proposal to elaborate activities involving literary texts, in which they should remove mathematical content, thus establishing a congruence and thus breaking a taboo of distinction between these Two disciplines. Authors such as GRANDO (2004), CARVALHO (1992), BRASIL (2002) and other authors based their theoretical knowledge.